Lysine methyltransferase Kmt2d regulates naive CD8+ T cell activation-induced survival - Kim, Jaekwan; Nguyen, Thomas; Cifello, Jeffrey; Ahmad, Raheel; Zhang, Yongqing; Yang, Qian; Lee, Ji-Eun; Li, Xiang; Kai, Yan; De, Supriyo; Peng, Weiqun; Ge, Kai; et al. (Frontiers in Immunology, 2023)
Lysine specific methyltransferase 2D (Kmt2d) catalyzes the mono-methylation of histone 3 lysine 4 (H3K4me1) and plays a critical role in regulatory T cell generation via modulating Foxp3 gene expression. Here we report a role of Kmt2d in naïve CD8+ T cell generation and survival. In the absence of Kmt2d, the number of CD8+ T cells, particularly naïve CD8+ T cells (CD62Lhi/CD44lo), in spleen was greatly decreased and in vitro activation-related death significantly increased from Kmt2dfl/flCD4cre+ (KO) compared to Kmt2dfl/flCD4cre- (WT) mice. Furthermore, analyses by ChIPseq, RNAseq, and scRNAseq showed reduced H3K4me1 levels in enhancers and reduced expression of apoptosis-related genes in activated naïve CD8+ T cells in the absence of Kmt2d. Finally, we confirmed the activation-induced death of antigen-specific naïve CD8+ T cells in vivo in Kmt2d KO mice upon challenge with Listeria monocytogenes infection. These findings reveal that Kmt2d regulates activation-induced naïve CD8+ T cell survival via modulating H3K4me1 levels in enhancer regions of apoptosis and immune function-related genes.